ETOS KERJA KEPALA SEKOLAH MTs RAUDHATUL QUR’AN PAYARAMAN KABUPATEN OGAN ILIR SUMATERA SELATAN - yeni agustina (UNISAN JURNAL, 2024)
This study aims to find out about the work ethic of the MTs Raudhatul Qur’an Payaraman Kabupaten Ogan Ilir Sumatera Selatan madrasa heads. This type of research method is a qualitative descriptive research, namely research procedures that produce descriptive data. Implicitly, the link between the improvement of the teacher’s work ethic and the head of the madrasa at MTs Raudhatul Qur’an Payaraman Kabupaten Ogan Ilir Sumatera Selatan are indeed two inseparable things, meaning that as a policy maker a madrasah head does not walk alone. That the involvement of all madrasa stakeholders in efforts to improve the work ethic at MTs Raudhatul Qur’an Payaraman Kabupaten Ogan Ilir Sumatera Selatan is very much a benchmark for this improvement. Preventive steps towards improving the work ethic at MTs Raudhatul Qur’an Payaraman Kabupaten Ogan Ilir Sumatera Selatan are very diverse. This shows that the efforts of the madrasa head in influencing, inviting and stimulating all madrasa stakeholders towards improving the quality of work are very maximal. From some of the descriptions it is explained that discipline is an important point in improving the work ethic at MTs Raudhatul Qur’an Payaraman Kabupaten Ogan Ilir Sumatera Selatan because from discipline many leaders, institutions and so on have become big because they feel and make discipline a barometer of progress.